Heterogeneity and specificity of cloned lines of influenza-virus specific cytotoxic T lymphocytes (The Rockefeller University Press, 1981)
Continuous lines of murine cytotoxic T lymphocytes (CTL) directed to type A influenza viruses have been generated in vitro by stimulation of individual CTL precursors in the presence of T cell-growth factor TCGF and syngeneic virus-infected stimulator cells. The cloned CTL lines are H-2 restricted in their target cell recognition and exhibit distinct patterns of influenza virus recognition. All CTL lines appear to be restricted in target cell recognition to either the H-2K or the H-2D end of the appropriate H-2 haplotype. Likewise, CTL lines of F1 origin are restricted in recognition exclusively to one of the parental haplotypes. All CTL lines examined express the Thy-1.2 and the Lyt-2- surface antigen markers. 4 of 11 cytotoxic lines examined also expressed detectable levels of the Lyt-1- surface antigen. These findings confirm at the clonal level previous observations on the H- 2K/D restriction of virus-specific CTL and also demonstrate heterogeneity among H-2 restricted CTL both from the standpoint of viral antigen recognition and cell surface phenotype.